FROST INVESTIGATION 1944-1945. APPENDIX 2. REPORT ON PRESQUE ISLE AIRFIELD, PRESQUE ISLE, MAINE. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1945)
The purpose of the investigation was the determination of development of frost action in the soils underlying airfield pavements as affected by various conditions of weather, soils, and ground water. The report presents the results of the frost investigation conducted at Presque Isle Airfield, Presque Isle, Maine during the period from 22 October 1944 through 16 June 1945. (Author) See also AD-712 533, Appendix 1, AD-712 362 and Appendices 3/4, AD-712 426.